Identification of Lactic Acid Bacteria from Fermented Kimchi Sawi Ansabi (Brassica juncea L.) using Phenotypic Similarities - Selly Marselina Teul; Rahmawati Rahmawati; Siti Ifadatin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Latic acid bacteria play a significant role in the fermentation of food, such as kimchi, which is fermented vegetables. Sawi kampung ansabi is a vegetable cultivated by the Dayak people in Kalimantan during the rice farming season which can be fermented into kimchi. Based on phenotypic similaities, the aim of this study was to identify and acquire cultures of lactic acid bacteria on MRSA media (De Man Rogosa and Sharpe Agar) enriched 1% CaCO3 from kimchi sawi ansabi fermented food sawi ansabi. The results of the isolations were used to test 10 isolates of lactic acid bacteria using the MVSP (Multivariate Statistical Package) program, the UPGMA (Unweighted Pair Group Method with Arithmetic Average Mean) method based on the Simple Matching Coefficient and Jaccard Coefficient to form dendrograms. Simple Matching Coefficient analysis resulted 8 isolates suspected to be Lactobacillus plantarum with a similarity index of 94.6%, 1 suspected 91.9% to Lactobacillus dellbrueckii, and 1 suspected 91.9% to Pediococcus cerevisiae. The Jaccard Coefficient analysis resulted in 8 isolates suspected of Lactobacillus plantarum with a similarity index of 92.6%, 1 isolate suspected 87% to Lactobacillus dellbrueckii, and 1 isolate 88% to Pediococcus cerevisiae.